PENERAPAN DIAGRAM KONTROL MULTIVARIATE EXPONENTIALLY WEIGHTED MOVING AVERAGE (MEWMA) PADA PENGENDALIAN KARAKTERISTIK KUALITAS AIR (Studi Kasus: Instalasi Pengolahan Air III PDAM Tirta Moedal Kota Semarang) - Anastasia Arinda; Mustafid Mustafid; Moch. Abdul Mukid (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Water treatment is intended to change the original water quality that does not fulfill the health requirements become a water for human consumption and must comply with the levels of certain parameters. Quality control can be done by forming a Multivariate Exponentially Weighted Moving Average (MEWMA) control chart. In the Multivariate Exponentially Weighted Moving Average (MEWMA) control charts with λ = 0.25 and UCL = 13.92658 seen that process controlled statistically. Once the process is under control, it can be done analysis of the ability of the process to determine whether the process fulfill the specifications or not. In the calculation process capability univariate each characteristics and multivariate process capability index values obtained more than 1 means that the process is going well. Keywords: water quality, Multivariate Exponentially Weighted Moving Average (MEWMA), process capability.